Electron Scattering from Disordered Grain Boundaries in Degenerate Polycrystalline Al‐Doped ZnO Thin Films. Issue 5 (17th April 2018) - Minami, Tadatsugu; Miyata, Toshihiro; Tokunaga, Hiroki
Abstract : This paper describes the influence of electron scattering from disordered grain boundaries on the carrier transport in polycrystalline Al‐doped ZnO (AZO) thin films prepared with electron concentrations on the order of 10 20  cm −3 . It is found that in degenerate AZO thin films prepared on glass substrates by various magnetron sputtering depositions, the mobility–carrier concentration ( µ Hall – n Hall ) relationship with a positive slope ( µ Hall increases as n Hall increases) is always obtained when measured by changing the sputter gas pressure and the substrate temperature, the location on the substrate surface, and the exposure time in a moisture‐resistance test. The main scattering mechanism, which limits the carrier transport in AZO thin films, is attributed to grain boundary scattering caused by the reflection of electrons from the potential barrier at the grain boundary between crystallites. The measured µ Hall – n Hall relationship demonstrates fair agreement with the relationship calculated using the Mayadas and Shatzkes (MS) theory. However, conceptual and other difficulties to apply the semi‐classical MS theory to degenerate semiconductors must be considered. The results of this quantum theory‐based investigation show that the positively sloped µ Hall – n Hall relationship attributes to Anderson localization, induced by electron grain boundary scattering from disordered successive grains. Abstract : This paper describes the influence of electron scattering from disordered grain boundaries on the carrier transport in polycrystalline Al‐doped ZnO (AZO) thin films prepared with electron concentrations on the order of 10 20  cm −3 . The results of this quantum theory‐based investigation shows that the positively sloped µ Hall – n Hall relationship attributes to Anderson localization, induced by electron grain boundary scattering from disordered successive grains.